Observation of atmospheric CO2 and CO at Shangri-La station: results from the only regional station located at southwestern China. Issue 1 (1st December 2016) - Fang, Shuangxi; Tans, Pieter P.; Steinbacher, Martin; Zhou, Lingxi; Luan, Tian; Li, Zou
Abstract : Mole fractions of atmospheric carbon dioxide (CO2 ) and carbon monoxide (CO) have been continuously measured since September 2010 at the Shangri-La station (28.02 ° N, 99.73 ° E, 3580 masl) in China using a cavity ring-down spectrometer. The station is located in the remote southwest of China, and it is the only station in that region with background conditions for greenhouse gas observations. The vegetation canopy around the station is dominated by coniferous forests and mountain meadows and there is no large city (population >1 million) within a 360 km radius. Characteristics of the mole fractions, growth rates, influence of long-distance transport as well as the Weighted Potential CO Sources Contribution Function (WPSCF) were studied considering data from September 2010 to May 2014. The diurnal CO2 variation in summer indicates a strong influence of regional terrestrial ecosystem with the maximum CO2 value at 7:00 (local time) and the minimum in late afternoon. The highest peak-to-bottom amplitude in the diurnal cycles is in summer, with a value of 18.2±2.0 ppm. The annual growth rate of regional CO2 is estimated to be 2.5±1.0 ppm yr −1 (1-σ), which is close to that of the Mt. Waliguan World Meteorological Organization/Global Atmosphere Watch (WMO/GAW) global station (2.2±0.8 ppm yr −1 ), that is also located at the Tibetan plateau but 900 km north. The CO mole fractions observed at Shangri-La are representative for both in large spatial scale (probably continental/subcontinental) and regional scale. The annual CO growth rate is estimated to be -2.6±0.2 ppb yr −1 (1-σ). But the CO rate of decrease in continental/subcontinental scale is apparently larger than the regional scale. From the back trajectory study, it could be seen that the atmospheric CO mole fractions at Shangri-La are subjected to transport from the Northern Africa and Southwestern Asia sectors except for summer and part of autumn. The WPSCF analysis indicates that the western and southwestern areas of the Shangri-La station (India, Myanmar and Bangladesh) may be the most important CO sources.